Why Does Fashion Fit China So Much? - Scaini, Luca; Belhaddad, Maria (European Scientific Journal, ESJ, 2022)
The paper focuses on investigating the relationship of the cause and effect between cultural behavior and physioeconomy of fashion in China. The purpose is to identify which cultural reasons lie behind the massive adoption of fashion in China, entrusting to these the success of fashion pulling fashion. The methodology adopted is an exploratory comparative analysis between nations (China, Japan, and India) which have cultural physioeconomic similarities, both genuine and artifact. The paper starts from an initial direct observation of the phenomena, checked through a bibliographic review of the background throughout the last 30 years, and supported by a survey supporting the hypothesis. Findings show that fashion was adopted for anthropological reasons of cultural homologation, and not for differentiation due to the specific socio-psychological and cultural structure of the Chinese Nation, similarly to Japan but contrarily to India. The difference in attitudes toward fashion is motivated by cultural reasons. The value of the paper is the exploratory investigation of anthropological behavior, which offers a scoped analysis with practical interest for socially based commodities and following the research course of the motivations behind buying fashion and China. This study is interesting as it will lead to a deeper quantitative research.